Clinicopathologic features and treatment outcomes of patients with fibrillary glomerulonephritis: A case series. Issue 20 (21st May 2021) - Marinaki, Smaragdi; Tsiakas, Stathis; Liapis, George; Skalioti, Chrysanthi; Kapsia, Eleni; Lionaki, Sophia; Boletis, John
Abstract : Abstract: Fibrillary glomerulonephritis (FGN) is a diverse glomerular disease with poor renal prognosis. The optimal therapeutic approach remains undetermined, as treatment outcomes vary across different studies. We retrospectively reviewed the medical data of 10 patients diagnosed with biopsy-proven FGN at our center between 2004 and 2019. Clinical and histological features, as well as therapeutic regimens and treatment response, are reported. The patients were predominantly men (2.5/1 men-female ratio) with a mean age at diagnosis of 46.5 years (IQR: 41.5-59.5). The median proteinuria and creatinine levels at presentation were 2.55 g/day (IQR: 0.4-8.9) and 1.35 mg/dl (IQR: 0.94–1.88), respectively. Four out of 10 patients presented with nephrotic syndrome, 5 patients with nephritic syndrome and 1 with isolated microscopic hematuria. Light microscopy showed mesangial proliferative (n = 7), membranoproliferative-like (n = 2), and diffuse sclerosing patterns (n = 1). Rituximab was used in 7/10 patients, either as monotherapy (n = 3) or combined with cyclophosphamide and corticosteroids (n = 4). Patients who were treated with immunosuppression had higher median levels of creatinine (1.40 mg/dl) and proteinuria (3.5 g/d) compared to those who received supportive treatment alone (0.94 mg/dl and 0.6 g/d, respectively). After a median follow-up of 30 months (IQR:18–66.5), 4 out of 7 patients (57%) treated with immunosuppression achieved a clinical response, 1 had persistent renal dysfunction and 2 patients progressed to end-stage renal disease. The present case series extends the existing literature on the clinical features and outcomes of FGN, as well as the use of rituximab-based regimens for the treatment of the disease. Further research is needed to establish the proper management of the disease.